ANALISIS PELAKSANAAN PEMBELAJARAN TATAP MUKA TERBATAS (PTMT) PADA ERA NEW NORMAL TERHADAP HASIL BELAJAR MATEMATIKA SISWA MADRASAH ALIYAH - Dewi Masyithoh; Nurul Arfinanti (SIGMA: JURNAL PENDIDIKAN MATEMATIKA, 2021)
During the Covid-19 pandemic, the Government of Indonesia made the policy described in circular No. 4 of 2020 on the Implementation of Education Policy in the Emergency Period of Corona Virus Disease (COVID-19), which is learning activities conducted online or online. The Government of Indonesia created a program for the sustainability of learning activities, namely Distance Learning (PJJ). Then the government issued a new policy on the implementation of limited face-to-face learning that can be implemented from July 2021. PTM is limited to 2 to 3 meetings in 1 week. For one face-to-face meeting there are 3 hours of lessons, combined with PJJ. Therefore, this study intends to analyze the extent to which the success of face-to-face learning is limited to the new normal to the results of student mathematics learning, so that an overview can later be used as a reference and further improvement material for Madrasah during limited PTM adaptation. The research method used is qualitative research. The study was conducted in November 2021.The location of the study is Madrasah Aliyah Negeri 2 Kulon Progo.The subject of this study is students of class XI MIPA 2 even and odd school year 2020/2021 numbered 28 children. Research nstruments are used using field observations, interviews, tests, and field records. Students' learning outcomes meet the classical minimum completion criteria. The data obtained shows that the average learning outcome of students' mathematics is 83.3 with the completion of learning classically only 100%.Thus the student's mathematical learning outcomes can be categorized into sufficient categories. The implementation of ptm limited in MA Negeri 2 Kulon Progo is well implemented.This is in accordance with limited PTM implementation guidelines during the new normal period which of course by applying strict health protocols.